Hydrophobicity and Adhesion of Aggregated Diamond Particles. Issue 5 (3rd March 2021) - Yao, Kaili; Dai, Bing; May, Paul W.; Tan, Xiaojun; Han, Jiecai; Zhu, Jiaqi
Abstract : Diamond Powders Diamond powders with high hydrophobicity and adhesion can be prepared by etching graphite plates using H2 /Ar plasma. The water contact angle of the diamond powders can reach 146.9°. The diamond surface can suspend 40 μL of water under a tilt angle of 180°. Such aggregated diamond powders are promising for no‐loss liquid transportation. More details can be found in article number 2000355 by Bing Dai, Jiaqi Zhu, and co‐workers.